PERISTILAHAN DALAM ACARA BATALAH MASYARAKAT DAYAK KANAYATN BAHASA AHE - Flavianus Yogi Indrayana; Patriantoro Patriantoro; Laurensius Salem (Universitas Tanjungpura, 2019)
AbstractTerminology on Batalah ceremony in Dayak community Kanayatn Ahe language Kabupaten Landak. Language and Arts Education Study Program. Faculty of Teacher Training and Education Tanjungpura University Pontianak. First advisor, Dr. Patriantoro, M.Hum. and Second advisor Dr. Laurensius Salem, M.Pd. Batalah is naming ceremony to a newborn child by Dayak Kanayatn community, Kabupaten Landak. Batalah ceremony activity process starts from the preparation, implementation, and post-implementation. The problems in this research are how the form of terminology in the Batalah ceremony, the lexical meaning, the cultural meaning, and the form of the text produced as a supplement for Indonesian learning teaching materials. The purpose of this research is describing the terminology on Batalah ceremony in Dayak community Kanayatn Ahe language Kabupaten Landak. The method used in this research is descriptive with qualitative research form. The analysis is carried out based on the problem in the research which includes the terminology of the preparation, implementation, and post-implementation. Based on the data analysis there are 97 terminologies on Batalah ceremony in Dayak community Kanayatn Ahe language Kabupaten Landak. There are 42 data of lexical meaning and 48 data of cultural meaning. Keywords: Terminology, Batalah, Dayak Kanayatn Ahe language.